Standardized reporting on studies of psychiatric pharmacist interventions - Brittany L. Parmentier, PharmD, MPH, BCPS, BCPP; Jonathan F. Lister, PharmD, BCPP; Tera D. Moore, PharmD, BCACP; Kristina Reinstatler, PharmD, MBA, BCPP; Ranel Troy Santos, PharmD, BCPP; Gregory H. Payne, MBA, CAE (American Association of Psychiatric Pharmacists, 2024)
Reporting interventions thoroughly and consistently in the literature allows for study reproducibility or implementation of the intervention into practice. Although there is currently no standard for describing Board-Certified Psychiatric Pharmacist (BCPP) interventions in the published literature, there are multiple checklists or guides that have been developed for reporting clinical interventions, including the template for intervention description and replication and the pharmacist patient care intervention reporting (PaCIR) checklist, that seek to improve the quality of reporting interventions in the literature. The purpose of this paper is to describe a proposed guide for reporting BCPP interventions in the literature by expanding the PaCIR checklist. Authors use a logic model developed by the American Association of Psychiatric Pharmacists to ensure all elements of the process are addressed in the expanded guide.